Total, subtotal and proximal gastrectomy in cancer a color atlas - Siquini, Walter; Ridolfo, Raffaella; Stortoni, Pierpaolo; Feliciotti, Emilio (Milano : Springer Italia, 2015)
This richly illustrated volume describes the performance of total and subtotal gastrectomy with extended D2 lymphadenectomy by providing a detailed step-by-step guide to both manual and mechanical procedures. Gastric cancer is the fourth most commonly occurring cancer and the second most common cancer-related cause of death worldwide, and surgery remains the only potentially curative treatment. Although several aspects of surgical management are still controversial, all guidelines for the treatment of curable gastric cancer recommend subtotal gastrectomy (for tumors located in the antrum and corpus) or total gastrectomy (for tumors located in the fundus) with extended D2 lymphadenectomy. Various technical tips and secrets are revealed that serve to simplify the procedure and simultaneously make it more effective: by rendering esophagojejunal and gastrojejunal anastomosis more secure, the risk of leakage is minimized. High-quality intraoperative color photographs and drawings covering all steps facilitate understanding of these complex operations and will prove an invaluable tool for surgeons, residents and professionals in the field.
Zweigstelle: Medizinische Bibliothek
Exemplar/Standort: WO 105 Siqui (MedBib)
Exemplar/Standort: Medizinische Bibliothek
Keywords: Gastrektomie; Magenresektion; Chirurgie; Viszeralchirurgie; Atlas